ANALYSIS OF LISTENING ABILITY OF CHILDREN IN GROUP B KINDERGARTEN BUNGONG SEULEUPOK SYIAH KUALA BANDA ACEH WITH THE AID OF AUDIO VISUAL MEDIA - Riza Oktariana; Rossiana Br Ginting (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
Listening ability is the process of listening, recognizing, and interpreting spoken symbols. The formulation of the problem in this study is how the listening ability of group B children at Bungong Seuleupok Syiah Kuala Kindergarten Banda Aceh is assisted by audio-visual media. The aim is to determine the listening ability of group B children at Bungong Seuleupok Syiah Kuala Kindergarten Banda Aceh with the help of audio-visual media. The instruments used in this study were interview sheets and documentation, with a sample size of four children in group B. Then the data was analyzed using a qualitative descriptive method. The results of the study showed that the analysis of the research on the listening ability of group B children assisted by audio-visual media at Bungong Seuleupok Syiah Kuala Kindergarten Banda Aceh did not experience any problems. So the researcher can conclude that the listening ability of group B children at Bungong Seuleupok Syiah Kuala Kindergarten Banda Aceh is included in the audio-visual learning character.